Physical match performance of Japanese top-level futsal players in different categories and playing positions - Ohmuro, T.; Iso, Y.; Tobita, A.; Hirose, S.; Ishizaki, S.; Sakaue, K.; Yasumatsu, M. (Biology of Sport, 2020)
To examine the substitution characteristics during official matches and the physical match performances of Japanese top-level futsal players in different categories and playing positions. Overall, 79 adult (age: 28.4 ± 4.6 years) and 59 youth (age: 17.1 ± 0.7 years) futsal players were classified into three groups based on the playing position (Pivot, Winger, and Defender). Physical match performance was assessed using active profiles from the semi-automatic tracking system. Speed and total distance covered were analysed for the in-play time. The in-play time was categorized based on the teams` ball possession status. The average total playing time per substitution was significantly higher in the youth (6.2 ± 2.1 min) than in the adult players (3.8 ± 1.1 min; p < 0.05). Furthermore, the proportion of high intensity exercise during matches was significantly higher in adults (43.2 ± 5.2%) than in youth players (37.2 ± 5.4%; p < 0.05). There was no significant difference in the average total distance covered between different playing positions. However, the average total distance covered with ball possession by Pivot (140 ± 15 m/min) was significantly lower than that by Winger (151 ± 15 m/min; p < 0.05) in adult players. Furthermore, the proportion of high intensity exercise without ball possession as Defender (36.7 ± 6.1%) was lower than that as Winger (41.9 ± 6.1%; p < 0.05) in adults but not in the youth players. Adult futsal players have higher physiological demands than youth players. The physical match performances vary between playing positions with or without ball possession. These results could be useful for youth development and position-specific training information.